ESPEN micronutrient guideline. Issue 6 (June 2022) - Berger, Mette M.; Shenkin, Alan; Schweinlin, Anna; Amrein, Karin; Augsburger, Marc; Biesalski, Hans-Konrad; Bischoff, Stephan C.; Casaer, Michael P.; Gundogan, Kursat; Lepp, Hanna-Liis; de Man, Angélique M.E.; Muscogiuri, Giovanna; et al.
Summary: Background: Trace elements and vitamins, named together micronutrients (MNs), are essential for human metabolism. Recent research has shown the importance of MNs in common pathologies, with significant deficiencies impacting the outcome. Objective: This guideline aims to provide information for daily clinical nutrition practice regarding assessment of MN status, monitoring, and prescription. It proposes a consensus terminology, since many words are used imprecisely, resulting in confusion. This is particularly true for the words "deficiency", "repletion", "complement", and "supplement". Methods: The expert group attempted to apply the 2015 standard operating procedures (SOP) for ESPEN which focuses on disease. However, this approach could not be applied due to the multiple diseases requiring clinical nutrition resulting in one text for each MN, rather than for diseases. An extensive search of the literature was conducted in the databases Medline, PubMed, Cochrane, Google Scholar, and CINAHL. The search focused on physiological data, historical evidence (published before PubMed release in 1996), and observational and/or randomized trials. For each MN, the main functions, optimal analytical methods, impact of inflammation, potential toxicity, and provision during enteral or parenteral nutrition were addressed. The SOP wording was applied for strength of recommendations. Results: There was a limited number of interventional trials, preventing meta-analysis and leading to a low level of evidence. The recommendations underwent a consensus process, which resulted in a percentage of agreement (%): strong consensus required of >90% of votes. Altogether the guideline proposes sets of recommendations for 26 MNs, resulting in 170 single recommendations. Critical MNs were identified with deficiencies being present in numerous acute and chronic diseases. Monitoring and management strategies are proposed. Conclusion: This guideline should enable addressing suboptimal and deficient status of a bundle of MNs in at-risk diseases. In particular, it offers practical advice on MN provision and monitoring during nutritional support.